A challenging palliation via novel therapeutic approach for unusual presenting with gingival metastasis from renal cell carcinoma relapsed eight years after nephrectomy - Aydın, Asım Armağan; Alparslan, Ahmet Şükrü; Ayık, Hülya; Kayıkçıoğlu, Erkan; Öztürk, Banu (The European Research Journal, 2018)
Renal cell carcinoma (RCC) is the third most frequently seen primary source of metastatic lesions of the oral cavity. Still oral cavity metastasis is a rarely seen clinical manifestation during the course of RCC. In a patient with a known history of RCC, in the presence of newly emerged oral and maxillofacial lesion(s), possibility of metastasis should be always thought of and pathological investigation should be performed as soon as possible. In RCC, metastatic involvement of oral cavity is generally accompanied by involvement of other organs with resultant lower chance of cure and poor prognosis. Especially in conditions which adversely affect functions of chewing and swallowing consequently nutrition and quality of life, surgery is contraindicated and local interventional methods transarterial chemoembolization, microwave ablation and radiofrequency ablation can be good palliative treatment alternatives. In advanced stages of the diseases with systemic involvement application of local interventional methods either solely or in combination with radiotherapy and surgery increases compliance to the systemic treatment and can contribute markedly to the prolongation of survival. Herein we aimed to present a case with unusual histopathological characteristics and presentation in whom we achieved a longer period of disease-free survival using a different local treatment method.